2022
DOI: 10.1177/10732748221131225
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency at Diagnosis Increases All-Cause and Prostate Cancer-specific Mortality in Jamaican Men

Abstract: Background 25 hydroxyvitamin D [25(OH)D] and serum calcium have been associated with incident prostate cancer (PCa). However, there is limited data on whether these metabolites predict survival in men of African descent, a population disproportionately affected by PCa. We studied the relationship of 25(OH)D at PCa diagnosis with all-cause and cancer-specific mortality among Jamaican men and examined whether serum calcium modified any associations. Methods Serum 25(OH)D from 152 Jamaican men with incident PCa w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…Elements such as VD itself and its associated enzymes, including VDR, have been shown to influence PCa proliferation, invasion, and resistance to treatment [ 7 10 ]. Retrospective clinical studies have underscored the significant correlation between abnormal serum vitamin levels and PCa prognosis [ 11 , 12 ]. Notably, a single-cell sequencing investigation conducted in genetically engineered Pten (i)pe−/− mice revealed that VD analogs can induce apoptosis in senescent prostatic intraepithelial neoplasia and diminish the infiltration of myeloid-derived suppressor cells within the prostate [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Elements such as VD itself and its associated enzymes, including VDR, have been shown to influence PCa proliferation, invasion, and resistance to treatment [ 7 10 ]. Retrospective clinical studies have underscored the significant correlation between abnormal serum vitamin levels and PCa prognosis [ 11 , 12 ]. Notably, a single-cell sequencing investigation conducted in genetically engineered Pten (i)pe−/− mice revealed that VD analogs can induce apoptosis in senescent prostatic intraepithelial neoplasia and diminish the infiltration of myeloid-derived suppressor cells within the prostate [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The potential role of 25(OH)D compounds in cancer's etiology and treatment has been explored since the early 1970s. Hamster models exhibited cancer development inhibition with 25(OH)D compound treatment, and human cancer cells showed the presence of the 25(OH)D receptor (VDR), associated with in vitro growth arrest [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%